Influence of Cutting Aspect on Continuous Use of Ni-Ti Orifice Opener - Toshifumi, OZAWA; Munehiro, MAEDA; Ichiroh, KATSUUMI (The Japanese Journal of Conservative Dentistry, 2014)
Purpose: Ni-Ti orifice openers were designed to prepare the coronal and middle third of canals. The purpose of this study was to compare the generated cutting torque after 10 continuous uses at two rotational speeds.  Methods: EndoWave .08 Ni-Ti rotary instruments (EW; J. Morita) and standardized straight root canal models were used in this study. The root canal model made of resin, which has a cut feeling similar to that of dentin, was used. A computer controlled torque testing device was used for this experiment. Instruments were inserted to a depth of 8 mm into the root canal. The rotational speed was fixed at 300 rpm and 600 rpm, respectively. The insertion speed into the root canal was set at 0.01 mm/sec. The torque generated under each experimental condition was recorded. The cutting blade was cleaned with a toothbrush after each use and was subjected to ultrasonic cleaning for five minutes. The same cutting procedure was repeated 10 times. Five root canal models were used for each experimental condition. The cutting efficacy was analyzed based on the torque-insertion distance and the variation in torque (ΔT) was calculated. The file was observed morphologically after the final cutting.  Results: The torque generated in root canal orifice enlargement was found to increase as the instrument was inserted further into the root canal. As shown by the torque-insertion distance curve of EW, the cutting torque increased with the number of cutting times. At both rotational speeds, ΔT tended to increase and cutting efficiency tended to decrease as the cutting time was increased. From observations of the cross section of the cutting part, wear was observed in the cutting edge after the final cutting, and this wear indicates increased ΔT.  Conclusion: These results suggested that prolonged use of EW .08 taper Ni-Ti rotary instruments significantly reduces their cutting efficiency.